Immunohistochemical evaluation of forkhead box A1 and EphA5 markers in serous ovarian carcinomas, and their impact on the clinical outcome of patients - Abouhashem, Nehal; Harb, Ola; Elwan, Amira; Zaitoun, Mohamed; Saraya, Yasser (Polish Journal of Pathology, 2022)
Ovarian cancer is the most lethal gynaecological neoplasm in females. In ovarian cancer, forkhead box A1 (FOXA1) aids transcription of YAP-associated protein mediated by the cyclic adenosine monophosphate response element-binding protein. As a result, cellular proliferation and migration increased. The roles of erythropoietin-producing human hepatocellular carcinoma cell (Eph) receptors and ephrin ligands in cell adhesion, migration, cell proliferation regulation in various cancers, and angiogenesis are well characterized. This study included formalin-fixed, paraffin-embedded tissue specimens from 41 patients with ovarian serous cystadenocarcinoma, including both low- and high-grade tumours. For each case, a paraffin block with tumour tissue was chosen for an immunohistochemical procedure using primary antibodies against EphA5 and FOXA1. By the end of 2017, patients finished their chemotherapy and were followed for the next 3 years. Positive FOXA1 and EphA5 results were presented in 68.3% and 39% of patients, respectively. A statistically significant correlation was detected between FOXA1 expression and each of CA-125 level, tumour stage, tumour grade, and the presence of lymph node metastasis. In our work, the overall survival was positively correlated with EphA5 expression and inversely correlated to FOXA1 immunoreactivity. The estimated disease-free survival (DFS) and EphA5 immunoreactivity had a significant positive association, whereas DFS and FOXA1 protein expression had a significant inverse link. FOXA1 and EphA5 expression play a role in ovarian cancer progression and prognosis prediction.